Transcriptional decomposition reveals active chromatin architectures and cell specific regulatory interactions - Sarah Rennie (Nature Portfolio, 2018)
Transcriptional regulation is coupled with chromosomal positioning and chromatin architecture. Here the authors develop a transcriptional decomposition approach to separate expression associated with genome structure from independent effects not directly associated with genomic positioning.